A telematics service discovery platform using the distributed peer‐to‐peer networking system. (6th May 2012) - Huang, Chung‐Ming; Yang, Chia‐Ching; Tseng, Chun‐Yu
SUMMARY In this paper, a distributed telematics peer‐to‐peer networking system is proposed to provide an efficient and feasible service discovery mechanism for mobile users. When mobile users travel on the road, they may request for some services from service providers to meet their demands. Mobile users in vehicles are assumed to go through a lot of regions, in which each region is associated with a region server. Related information of all service providers in a region is stored in its region server, and each region server is in charge of the service discovery requests from all vehicles located in its region. This paper focuses on the issues of developing a distributed peer‐to‐peer telematics service discovery networking system over the vehicular network environment for mobile users. To provide the communication mechanism for telematics service discovery among region server, mobile users, and service providers, the Telematics Service Markup Language is proposed. According to clients' demands, three types of query scenarios are proposed, which are (1) reference point based query, (2) continual query, and (3) route‐based query. Finally, we present usage examples and system implementation of distributed telematics peer‐to‐peer. Copyright © 2012 John Wiley & Sons, Ltd.